Pelayanan Administrasi Kependudukan di Kecamatan sampe Desa (PAKETAN PEDES) - Satrio Putro , Gagah Iman; An-Naharis Sakinah, Aulia Roviqoh (Najah: Journal of Research and Community Service, 2024)
Abstract Paketan Pedes facilitates the public in submitting population documents at the service counters of sub-districts or villages. The appointed village officials will process the submission online to the Population and Civil Registration Office. After the document is issued with the electronic signature of the Head of the Population and Civil Registration Office, the document can be printed at the sub-district or village. Thus, Paketan Pedes simplifies the population administration process and increases the accessibility of services for the community. This research uses the research methods of Literature Study, Observation, Interviews, and Data Analysis. With the Paketan Pedes, the public no longer needs to queue at the Population and Civil Registration Office, they can simply come to the village or sub-district with complete documents. Of course, this can save time and effort.